Acute exposure to wood smoke from incomplete combustion - indications of cytotoxicity - Muala, Ala; Rankin, Gregory; Sehlstedt, Maria; Unosson, Jon; Bosson, Jenny A.; Behndig, Annelie; Pourazar, Jamshid; Nyström, Robin; Pettersson, Esbjörn; Bergvall, Christoffer; Westerholm, Roger; Jalava, Pasi I.; et al. (Particle and fibre toxicology, 2015)
Background Smoke from combustion of biomass fuels is a major risk factor for respiratory disease, but the underlying mechanisms are poorly understood. The aim of this study was to determine whether exposure to wood smoke from incomplete combustion would elicit airway inflammation in humans. Methods Fourteen healthy subjects underwent controlled exposures on two separate occasions to filtered air and wood smoke from incomplete combustion with PM 1 concentration at 314 μg/m 3 for 3 h in a chamber. Bronchoscopy with bronchial wash (BW), bronchoalveolar lavage (BAL) and endobronchial mucosal biopsies was performed after 24 h. Differential cell counts and soluble components were analyzed, with biopsies stained for inflammatory markers using immunohistochemistry. In parallel experiments, the toxicity of the particulate matter (PM) generated during the chamber exposures was investigated in vitro using the RAW264.7 macrophage cell line. Results Significant reductions in macrophage, neutrophil and lymphocyte numbers were observed in BW ( p < 0.01, <0.05, <0.05, respectively) following the wood smoke exposure, with a reduction in lymphocytes numbers in BAL fluid (<0.01. This unexpected cellular response was accompanied by decreased levels of sICAM-1, MPO and MMP-9 ( p < 0.05, <0.05 and <0.01). In contrast, significant increases in submucosal and epithelial CD3+ cells, epithelial CD8+ cells and submucosal mast cells ( p < 0.01, <0.05, <0.05 and <0.05, respectively), were observed after wood smoke exposure. The in vitro data demonstrated that wood smoke particles generated under these incomplete combustion conditions induced cell death and DNA damage, with only minor inflammatory responses. Conclusions Short-term exposure to sooty PAH rich wood smoke did not induce an acute neutrophilic inflammation, a classic hallmark of air pollution exposure in humans. While minor proinflammatory lymphocytic and mast cells effects were observed in the bronchial biopsies, significant reductions in BW and BAL cells and soluble components were noted. This unexpected observation, combined with the in vitro data, suggests that wood smoke particles from incomplete combustion could be potentially cytotoxic. Additional research is required to establish the mechanism of this dramatic reduction in airway leukocytes and to clarify how this acute response contributes to the adverse health effects attributed to wood smoke exposure. Trial registration NCT01488500